The Common Bullying types on Students with Autism spectrum disorder and its reasons from their Teachers’ Perspectives in the city of Jeddah - Almalki, Walaa Awadh; Sahab, Lama AbdulHakeem (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the most common forms of school bullying against students with autism spectrum disorder according to the viewpoint of their teachers. The sample contained (139) male and female teachers. The researcher used the descriptive method and designed a questionnaire to identify the differences of bullying according to the variable of gender, and to know the reasons of bullying. The results indicated that the most common forms of school bullying against students with autism spectrum disorder according to the viewpoint of their teachers on the most dimensions of the study were medium (3.073) Arranged as follows social bullying, followed by verbal bullying, then electronic bullying, then property damage bullying, and finally physical bullying. There were not any significant statistical differences for forms of bullying due to the variable of gender. The results showed that the level of reasons of bullying against students with autism spectrum disorder according to the viewpoint of their teachers were great (4.044), which were arranged in descending order, as follows: Reasons related to the teacher of general education, then reasons related to students with autism spectrum disorder, then reasons related to peers, and then reasons related to the school environment.
Keywords: school bullying; Autism spectrum disorder; Forms of bullying